Fundacje architektoniczne rodziny Rozdrażewskich – problemy stylu i znaczenia formy - Miedziak, Witold (Artium Quaestiones, 2019)
The paper is a monograph of the churches founded by the Doliwita Rozdrażewski family, which make a significant percent of the total number of churches built in the region of Wielkopolska at the turn of the 17thcentury. Those churches, constructed under the supervision of Hieronim, Archbishop of Włocławek, and the Poznań Chamberlain Jan, have not been analyzed by scholars, and some of them have not been even mentioned in scholarly publications. The analysis presented in the paper allows one to consider the churches founded by the Rozdrażewski family in the context of the architecture of the region, Poland, and the neighboring countries. The features of the period, as well as a religious controversy among the family members, made it possible to approach a number of problems connected to contemporary artistic changes, such as the so-called “gothic style around 1600,” relations between Protestant and Roman Catholic architecture, and claims about the purposeful “archaism” of the architecture of the period, emulating the Romanesque or the Gothic style. Responding to the research postulates formulated by other scholars, the author proposed a new term, “early modern Gothic,” coined to replace other, ambiguous terms referring to the architecture of those times. Moreover, he proposed an innovative way of interpreting Gothic architecture of the early modern period, based on following its transformations from the end of the Middle Ages till the turn of the 17thcentury, which results in a claim that Gothic architecture continued until then.